2015
DOI: 10.1007/s10534-015-9855-7
|View full text |Cite
|
Sign up to set email alerts
|

Fusaric acid induces a notochord malformation in zebrafish via copper chelation

Abstract: Over a thousand extracts were tested for phenotypic effects in developing zebrafish embryos to identify bioactive molecules produced by endophytic fungi. One extract isolated from Fusarium sp., a widely distributed fungal genus found in soil and often associated with plants, induced an undulated notochord in developing zebrafish embryos. The active compound was isolated and identified as fusaric acid. Previous literature has shown this phenotype to be associated with copper chelation from the active site of ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…FA was discovered almost 80 years ago (Yabuta et al, 1937) and was the first fungal toxin whose production was detected in planta (G€ aumann, 1957). Its strong phytotoxicity (Niehaus et al, 2014;Stipanovic et al, 2011), moderate toxicity in animals (Porter et al, 1995;Yin et al, 2015) and bacteria (Bacon et al, 2006;Ruiz et al, 2015), and its pharmacological properties (Song and Yee, 2001;Wang and Ng, 1999), make the study of FA biosynthesis and regulation of great interest. Moreover, FA inhibits the growth of fungi, including its producer Fusarium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FA was discovered almost 80 years ago (Yabuta et al, 1937) and was the first fungal toxin whose production was detected in planta (G€ aumann, 1957). Its strong phytotoxicity (Niehaus et al, 2014;Stipanovic et al, 2011), moderate toxicity in animals (Porter et al, 1995;Yin et al, 2015) and bacteria (Bacon et al, 2006;Ruiz et al, 2015), and its pharmacological properties (Song and Yee, 2001;Wang and Ng, 1999), make the study of FA biosynthesis and regulation of great interest. Moreover, FA inhibits the growth of fungi, including its producer Fusarium.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of FA to chelate metal ions, such as iron or copper, has been known for a long time (Lakshminarayanan and Subramanian, 1955;Malini, 1966;Pan et al, 2010;Tamari and Kaji, 1952). In a recent study, FA has been shown to chelate different metal ions, including Fe 21 , Fe 31 , Cu 21 , Mn 21 and Zn 21 (Ruiz et al, 2015;Yin et al, 2015). We thus asked whether the production of FA is required for the growth of F. oxysporum under metallimiting conditions.…”
Section: Effect Of Ph and Nutrients On Fub1 Transcript Levels And Fa mentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of serotonin results from its impaired regulation and consequently amplifies behaviors distinctive of the firing of serotonergic neurons such as loss of appetite and lethargy 32 . In zebrafish, FA induced teratogenic effects by inhibition of lysyl oxidase (a copper-dependent enzyme) 33 . FA also decreased norepinephrine levels in the brain, heart, spleen and adrenal gland of rats 34 .…”
Section: Introductionmentioning
confidence: 99%
“…It has anti-hypertensive activity in cats, dogs, rabbits, and rats by inhibiting the copper-dependent enzyme dopamine b-hydroxylase, a key enzyme in the synthesis of the neurotransmitter norepinephrine [Hidaka et al, 1969;Terasawa and Kameyama, 1971]. Fusaric acid was also shown to be toxic to zebrafish by chelating copper and inhibiting the enzyme lysyl oxidase resulting in notochord malformation [Yin et al, 2015]. Fusaric acid was also shown to be toxic to zebrafish by chelating copper and inhibiting the enzyme lysyl oxidase resulting in notochord malformation [Yin et al, 2015].…”
mentioning
confidence: 99%